Transposon‐mediated transgenesis, transgenic rescue, and tissue‐specific gene expression in rodents and rabbits. Issue 3 (29th November 2012) - Katter, Katharina; Geurts, Aron M.; Hoffmann, Orsolya; Mátés, Lajos; Landa, Vladimir; Hiripi, László; Moreno, Carol; Lazar, Jozef; Bashir, Sanum; Zidek, Vaclav; Popova, Elena; Jerchow, Boris; et al.
Abstract : Germline transgenesis is an important procedure for functional investigation of biological pathways, as well as for animal biotechnology. We have established a simple, nonviral protocol in three important biomedical model organisms frequently used in physiological studies. The protocol is based on the hyperactive Sleeping Beauty transposon system, SB100X, which reproducibly promoted generation of transgenic founders at frequencies of 50–64, 14–72, and 15% in mice, rats, and rabbits, respectively. The SB100X‐mediated transgene integrations are less prone to genetic mosaicism and gene silencing as compared to either the classical pronuclear injection or to lentivirus‐mediated transgenesis. The method was successfully applied to a variety of transgenes and animal models, and can be used to generate founders with single‐copy integrations. The transposon vector also allows the generation of transgenic lines with tissue‐specific expression patterns specified by promoter elements of choice, exemplified by a rat reporter strain useful for tracking serotonergic neurons. As a proof of principle, we rescued an inborn genetic defect in the fawn‐hooded hypertensive rat by SB100X transgenesis. A side‐by‐side comparison of the SB100X‐ and piggyBac ‐based protocols revealed that the two systems are complementary, offering new opportunities in genome manipulation.—Katter, K., Geurts, A. M., Hoffmann, O., Mátés, L., Landa, V., Hiripi, L., Moreno, C., Lazar, J., Bashir, S., Zidek, V., Popova, E., Jerchow, B., Becker, K., Devaraj, A., Walter, I., Grzybowksi, M., Corbett, M., Rangel Filho, A., Hodges, M. R., Bader, M., Ivics, Z., Jacob, H. J., Pravenec, M., Bősze, Z., Rülicke, T., Izsvák, Z. Transposon‐mediated transgenesis, transgenic rescue, and tissue‐specific gene expression in rodents and rabbits. FASEB J. 27, 930–941 (2013). www.fasebj.org